Total ankle replacement in patients with haemophilia and virus infections – a safe alternative to ankle arthrodesis?. (3rd March 2014) - Strauss, A. C.; Goldmann, G.; Wessling, M.; Gravius, S.; Müller, M. C.; Wimmer, M. D.; Wirtz, D. C.; Oldenburg, J.; Pennekamp, P. H.
Summary Despite reliable results of ankle fusion for advanced haemophilic arthropathy, total ankle replacement (TAR) may be functionally advantageous. There is only very limited literature data available on TAR in patients with haemophilia. The objective of this study is to evaluate the short‐ and mid‐term results after TAR in patients with end‐stage haemophilic ankle arthropathy and concomitant virus infections. In a retrospective study, results after eleven TAR in 10 patients with severe (n = 8) and moderate (n = 2) haemophilia (mean age: 49 ± 7 years, range, 37–59) were evaluated at a mean follow‐up of 3.0 years (range, 1.2–5.4). Nine patients were positive for hepatitis C, five were HIV‐positive. Range of motion (ROM), AOFAS‐hindfoot‐score, pain status (visual analogue scale, VAS) as well as patient satisfaction were evaluated. In two cases deep prosthesis infection occurred leading to the removal of the implant. In the remaining eight patients the mean AOFAS score improved significantly from 21.5 to 68.0 points (P < 0.0005), the VAS score decreased significantly from 7.6 to 1.9 points (P < 0.0005). ROM increased from 23.2 to 25.0 degrees (P = 0.51). At final follow‐up all patients without any complications were satisfied with the postoperative results. Radiographic examination did not reveal any signs of prosthetic loosening. TAR is a viable surgical treatment option in patients with end‐stage ankle osteoarthritis due to haemophilia. It provides significant pain relieve and high patient satisfaction. However, due to the increased risk of infection and lack of long‐term results, TAR particularly in patients with severe haemophilia and virus infections should be indicated carefully.